(Un)willingness to communicate in English among Korean study abroad students in the Philippines - Quinto, Edward Jay M.; Ofalia, Bernardino; Bae, Jinho; Salonga, Lean Syhing (Penerbit Universiti Kebangsaan Malaysia, 2019)
Internationalization has prompted schools to send out students in study-abroad programs. Many inbound international students come to the Philippines often to learn the English language at lower tuition costs, lower costs of living, and well-trained teachers. Among Koreans, many feel strongly motivated to learn English, yet many remain unwilling to communicate in real-life situations. The researchers explore the notion of (un)willingness to communicate among ten Korean EFL learners in study abroad programs in Manila. Findings from an indepth focus group discussion support previous studies within the Korean social context, in that the participants generally exhibit unwilling-to-communicate tendencies. Three themes that explain this phenomenon were identified: communicative situation’s level of formality, learners’ intercultural sensitivity, and their subject matter anxiety. Both level of formality and subject matter anxiety support willingness to communicate (WTC) as a situationally-dependent construct. However, intercultural sensitivity seemed to be a mixture of intercultural complex (IC) and L1 audience sensitivity (L1AS) previously found among learners within the Korean school system. It could then be that, as a factor of WTC in a study abroad context, intercultural sensitivity involves a knowledge of ‘Non-Korean world’, i.e., the Filipino language learning context, and an intense awareness of the inequalities perceived between Koreans and their Non-Korean audience. Results may assist communication coaches, international programs staff, and language teachers in minimizing the ‘generalized baggage’ that Korean learners carry around and bring with them when communicating in a foreign language.